Pengaruh Disiplin dan Motivasi Terhadap Produktivitas Kerja Karyawan Plant Cikarang U PT. Nippon Indosari Corpindo Tbk - Ranuyoga Arsyiandi; Ririn Uke Saraswati; Suripto Moh. Zulkifli; Khairil Anwar (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to determine the effect of work discipline and motivation on the productivity of Plant Cikarang U PT. Nippon Indosari Corporindo Tbk. Data were analyzed using validity, reliability, and multiple regression tests, with 76 samples taken from Plant U employees. The hypothesis was tested to apply the T test, F test, and the coefficient of determination. The findings of this study describe the regression equation y = 16,610 + 0.273x1 + 0.454 x2 + e. Variable analysis shows that work discipline has a score of 2,993> t table 1,294, work motivation has a t count score of 4,738> t Table 1,294. Partially disciplined and motivation has a significant positive effect on productivity through sig scores <0.05. Simultaneously, the three variables have F count 56,727> F table 2.38, and Sig 0,000 <0.05 shows a significant effect on employee work productivity. The independent variable explains 61.8% of variations in work productivity, while the remaining 38.2% are explained by other variables. It is recommended that companies increase discipline and employee work motivation to achieve productivity targets.